Land use and morphological changes in cuesta environment on the upper Capivara River basin – Botucatu (São Paulo. Brazil) - Higor Lourenzoni Bonzanini; Cenira Maria Lupinacci (Geografares, 2022)
From the advancement of human techniques, man has acted in the transformation of the earth’s surface, often accelerating the erosive dynamics. In steep and rugged terrains, such as the relief of cuestas from the interior of the São Paulo State, this problem can become more complex. Thus, the aim of this paper is to analyze the changes in land use pattern and changes in relief morphology that indicate acceleration in the development of erosive processes, in the Botucatu county (SP). For this purpose, geomorphological and land use maps were elaborated, that made it possible to define the geoindicators. The monitored geoindicators show a dynamic of linear erosive processes from changes in land use, which added sediments to the river system. The results obtained can assist environmental planning in the studied area and in areas with similar characteristics, identifying the patterns of anthropic interference in scenarios with the presence of cuesta relief.